2003
DOI: 10.1523/jneurosci.23-21-07958.2003
|View full text |Cite
|
Sign up to set email alerts
|

Diadenosine Tetraphosphate Protects against Injuries Induced by Ischemia and 6-Hydroxydopamine in Rat Brain

Abstract: Diadenosine tetraphosphate (AP4A), an endogenous diadenosine polyphosphate, reduces ischemic injury in the heart. In this study, we report the potent and protective effects of AP4A in rodent models of stroke and Parkinson's disease. AP4A, given intracerebroventricularly before middle cerebral artery (MCA) ligation, reduced cerebral infarction size and enhanced locomotor activity in adult rats. The intravenous administration of AP4A also induced protection when given early after MCA ligation. AP4A suppressed te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 25 publications
(33 reference statements)
5
50
0
Order By: Relevance
“…Oxidative stress induces synthesis of AP 4 A (41) . In vivo, AP 4 A reduced translocation of mitochondrial cytochrome C, activation of cytoplasmic caspase-3, and cerebral infarction in ischemic cerebral cortex in vivo (42) . These data suggest that AP 4 A is protective, via anti-apoptotic mechanisms, against ischemic injury in cerebral cortex.…”
Section: Ap 4 Amentioning
confidence: 86%
“…Oxidative stress induces synthesis of AP 4 A (41) . In vivo, AP 4 A reduced translocation of mitochondrial cytochrome C, activation of cytoplasmic caspase-3, and cerebral infarction in ischemic cerebral cortex in vivo (42) . These data suggest that AP 4 A is protective, via anti-apoptotic mechanisms, against ischemic injury in cerebral cortex.…”
Section: Ap 4 Amentioning
confidence: 86%
“…Inosine, as well as adenosine, reduced astroglial injury in ischemia, and it was suggested that adenosine was acting after breakdown to inosine (Haun et al, 1996). The diadenosine polyphosphate Ap 4 A protects against injury induced by ischemia in rat brain through actions at P1 adenosine receptors (Wang et al, 2003b).…”
Section: Ischemiamentioning
confidence: 99%
“…Indeed, previous studies have indicated that Ap 4 A reduces ischemic injury in the CNS and heart (Khattab et al, 1998;Ahmet et al, 2000a,b;Wang et al, 2003). Recently, Ap 4 A has been shown to have strong neuroprotective properties mediated by P1 and P4 receptors in primary neuronal culture used as models for stroke and Parkinson's disease (Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%